Antiretroviral therapy (ART) coverage at public and private ART facilities in Myanmar. Issue 9 (2nd September 2021) - Nwe, Thet Wai; Lee, Sung-Jae; Li, Li; Hsan, May Thu Aung; Htwe, Aung Thu; Oo, Htun Nyunt; Detels, Roger
ABSTRACT: Myanmar's continuum of HIV care was surveyed to assess the National AIDS Control Programme's progress; according to its reports, ART coverage was 38% in 2014, 47% in 2015, and 56% in 2016. To evaluate ART coverage and gaps in care, a serial cross-sectional study used the national programme data reported between January 2014 and December 2016, including 228 public and 62 private ART facilities. ART coverage among PLHIV under 15 years old was 89% in 2014, 93% in 2015, and 88% in 2016. Retention in ART care among women was higher than among men, although women were more likely to discontinue care. PLHIV who were enrolled in ART facilities initiated ART at the rates of 60% in 2014, 68% in 2015, and 74% in 2016. Over the 3-year study period, these facilities reported that 2.5–3.7% of PLHIV taking ART had died, and that 3.3–4.8% were lost to follow-up. PLHIV who were tested for viral load were low (2.5–3%). The continuum of HIV care at ART facilities has improved, but more information about attrition and viral suppression are still needed. The reporting system for newly diagnosed PLHIV and facilities for viral load testing need to be strengthened.